HO‐1 As Modulator of the Innate Immune Response in Pregnancy. (22nd March 2013) - Kahlo, Kristina; Fill Malfertheiner, Sara; Ignatov, Tanja; Jensen, Federico; Costa, Serban‐Dan; Schumacher, Anne; Zenclussen, Ana C.
<x xml:space="preserve">Abstract</x> Problem The immune modulatory effect of heme oxygenase‐1 (HO‐1) is well documented in studies about sepsis and transplantation. This work evaluates the influence of HO‐1 on the innate immune response during pregnancy. Method of Study Human first‐trimester trophoblasts derived from normal pregnancies or spontaneous abortions were analyzed for their basal HO‐1, BCL‐associated athanogene‐1 (Bag‐1), and cytokine production before and after LPS treatment. In vivo, pregnant Hmox1+/+ and Hmox1+/− female mice were treated with LPS, and the production of Bag‐1 was evaluated. Results Human trophoblasts up‐regulated the expression of both HO‐1 and pro‐inflammatory cytokines after LPS treatment, whereas the basal level of HO‐1 was higher in normal pregnancies. In vivo, HO‐1 deficiency provoked diminished Bag‐1 level upon LPS treatment. Conclusion HO‐1 deficiency causes an inflammatory immune reaction and diminished expression of protective molecules in trophoblasts. Thus, HO‐1 emerges as one important modulator of innate immune responses in pregnancy.